KEKUATAN HUKUM EKSEKUSI JAMINAN AKTA PENGAKUAN HUTANG DALAM PERJANJIAN KREDIT (STUDI PENELITIAN DI PT. BANK MANDIRI KANTOR CABANG PEMBANTU MATANG GEULUMPANG DUA KABUPATEN BIREUEN ACEH) - ASMAUL HUSNA (jurnal.unprimdn.ac.id, 2020)
In banking practice, a loan is usually realized in form of an agreement of acknowledgment of debt by debtor to creditor, in which the creditor acknowledges to have made a loan of some amount of money to a bank, under particular terms. When a debtor defaults, a creditor can file a request to Head of Court for execution of the contents of their agreement with a grosse deed because it has executorial force. However, in this research, the creditor does not directly execute the guarantee when the debtor defaults. Instead, they issue a Letter of Declaration of Willingness to discharge the rights over the collateral that is guaranteed and signed by the debtor. The research problems are how about the legal force of execution of collateral in a deed of acknowledgement of debt in a loan agreement, how about the legal consequences for the debtor in the deed of acknowledgement of debt in case of a default in a loan agreement in Matang Geulumpang Dua Village, and how about the legal efforts that can be made by the creditor in the execution of the collateral in the deed of acknowledgment of debt in the loan agreement.